Mengglobalkan Makanan Tradisional Lewat Media Sosial Youtube sebagai Budaya Tandingan (Studi Food Vlogger Nex Carlos sebagai Media Promosi Kuliner Lokal) - Rochmad Effendy; Putri Ayu Wulandari; Lian Agustina Setiyaningsih; Ana Mariani (Jurnal Nomosleca, 2021)
Globalization is the massive, systematic spread of American culture and its lifestyle throughout the world. The lifestyle of consuming fast food is constructe as a modern, current and global lifestyle through regulatory and deep capture with the sophistication of advertising propagated through communication media. Propaganda messages through communication media make cultural colonization by homogenizing food tastes in the world, so delegitimizes and distorts local food prestige. People no longer see traditional food as cultural identity. This study examines the effectiveness of YouTuber Carlos in popularizing traditional foods to foreign countries. The qualitative descriptive approach with observation, document and literatures reviews and interviews with informants. This study finds that Nex Carlos' Youtube account functions effectively in globalizing local food with well interactive communication and intimate emotional bonds. Para social interaction makes viewers to see food vlogger as role model, counselor, and entertained which eventually leads to recommended adoption. As a cultural product, local culinary consumption been seen as a counterculture to the incessant global fast food propaganda. Social learning about ecological, social and political awareness on food stock availability dubbed as food pedagogy needs to be on the next important agenda for guaranteeing the food sustainability. Keywords: Food Vlogger, Globalization, Homogenization, Para Social Interaction, Pedagogy of Food